HANSENÍASE NO ESTADO DO MARANHÃO:análise das estratégias de controle e os impactos nos indicadores epidemiológicos - Passos, Carlos Eduardo de Castro (2013)
Leprosy control strategies have been improving over the decades. However, in 2011, Brazil still has the largest number of leprosy cases in the Americas (93%) and ranks second case in the world, behind India and ahead of Indonesia. Strengthening this statistic is Maranhão, Brazil placed 4th in the detection of new cases, 3 children under 15 years of age and generally more prevalent in the northeast. This study aimed to analyze the epidemiological indicators recommended for monitoring and evaluation, describing strategies for leprosy control in the state of Maranhão. Thus, we developed a exploratory ecological study of the temporal evolution of the epidemiological leprosy and public policies to control the disease in the period 2002-2011. Regarding control strategies was observed that the state follows the recommendations of the Ministry of Health, however, with low resolution, the administrative and political difficulties for social abyss in which the state is. Identified the main epidemiological and operational indicators of leprosy, in which one might observe a trend of decreasing detection of new cases with strong statistical significance (R2 = 0,83, P <0,0001). On the other hand, new cases multibacillary revealed in inverse trend (R2 = 0,95, P <0,0001). Should be highlighted in the value of maintaining the proportion of cases with grade 2 disability at diagnosis generating a stable trend in the course of the study series. The analysis also showed that the ratio of new cases was significantly higher in Maranhão 74,3 / 100.000 in the country than the average 24,9 / 100.000 , with RR = 2,96 , 95% CI: 1,88 to 4,66 ; p < 0,0001 ; followed the same trajectory as the ratio of new cases in children under 15 years and the annual rate of prevalence. Regarding covariates case detection calls attention to the fall of the difference between the sexes, even keeping a significant difference with respect to male OR = 2,36 [ 95% CI 2,28 to 2,46 ] , p < 0,0001, and the stagnation of prevalence and incidence reason . It was also observed, keeping the number of cities in the five biennia hyperendemic situation of the study and the total period , causing the results pointed to a standard number of cases in the northwest not yet reported by other studies, central and western state, emonstrated by a vision of periods of study and map bubbles that can pass a real dimension of the disease in each municipality analyzed. Thus, the study reveals that even with the control strategies of leprosy undergoing constant maturation processes, leprosy continues as a neglected disease, hyperendemic diagnosed later in the study area with no prospect of exhausting these cases in the coming years, leading to believe that the process of social maturity is a big step towards achieving the goal of disease control.